Root coverage with apical tunnel approach using propolis as a root conditioning agent: A case report with 2‐year follow‐up and review of the literature - Obada Mandil; Hamoun Sabri; Neshatafarin Manouchehri; Diana Mostafa; Hom‐Lay Wang (Clinical and Experimental Dental Research, 2023)
Abstract Objectives One of the main challenges in performing root coverage is patient discomfort and donor site morbidity. This case report presents a minimally invasive apical tunnel surgical technique, with propolis for root conditioning, to correct gingival recession defects without harvesting donor grafts, flap elevation, or sutures. Propolis is a natural anti‐infective, anti‐inflammatory, and antioxidant agent. Material and Methods A 58‐year‐old woman with no significant medical history was presented for root coverage of her upper left canine and first premolar with recession type (RT)1A (+). Propolis was used as a root conditioning agent to promote soft tissue coverage via an apical tunnel approach. During the apical tunnel approach, a small apical hole was made 6 mm below the mucogingival junction, and the mucosa and associated attached gingiva was away from the tooth so the flap could be repositioned coronally. Collagen matrix was used as a soft tissue graft material. Results At the 2‐month, 6‐month, 8‐month, and 2‐year follow‐up, complete root coverage was achieved for both teeth. No bleeding on probing was noticed nor recurrent GRs at the treated sites. Conclusion Without incisions, donor site reflection, or flaps, the apical tunnel approach can be successfully used to cover the exposed roots. Additionally, propolis is a potential root conditioning agent during soft tissue graft procedure due to its anti‐inflammatory and antioxidant properties.